BUSINESS INCUBATION IN THE NATIONAL UNIVERSITY OF SAN MARCOS: A STRATEGY FOR EFFECTUATE ITS COMMITMENT TO ECONOMIC AND SOCIAL DEVELOPMENT OF THE COUNTRY - Gutiérrez Huby, Ana María (2012)
This study is about the enterprising incubation in universities that look for opinions from authorities, professors, and students in the Accounting Department in regards to the importance and necessity of the development of students who have entrepreneurial potential in the Accounting Department, helping the student with an alternative action that allows them to: canalize the most effective incaution between the university and the private sector, while at the same time to conceive it as one of the strategies that allows us to accomplish the institutional vision and the compromise with the social and economical development of the country. Among the exposed aspects considered are: the conceptualization of the company incubation, its evolution and level of development, characteristics and implications of the incubation process, moreover a revision of a country context and the social, economic, and academic conditions of the private sector program. We concluded that there are not enough universities that have an incubation program for entrepreneurial students, and the few that exist have to improve on their programs, Brazil and Mexico are the few countries that have these programs more so than any other country in desarrothe Latin American region. Entrepreneurial incubation is still a theme that is developing and it has to overcome challenges and limitations especially when it comes to lack of resources and insufficient.